Bipolar cautery forceps: An economical version - Aswin, Appukuttan; Jagadeesh, S. (Indian Journal of Plastic Surgery, 2007)
Context:Bipolar cautery forceps are an expensive instrument and especially in Government Medical colleges and Government Hospitals, getting a pair is a very tedious and prolonged task due to official reasons.Aims:To make a cheap and easily obtainable bipolar cautery forceps.Settings and Design: The reason for innovation was that the cautery forceps in the department were out of order and we were not getting replacements.Materials and Methods:Made from condemned and damaged forceps or from stainless steel nonsurgical forceps which are very low-cost, very cheap and easy to get hold of, especially in a Government institution with limited resources.Results: It has been used for the past one and a half years in our Department for plastic surgical procedures, including microvascular surgery. Initially, it was designed when the cautery forceps in the department were out of order and we were not getting replacements and later on, it became part of the routine set as it was found to be equally good.Conclusions: A very cheap and useful alternative to the commercially available bipolar cautery forceps has been made.
Keywords: Flexor tendon repair; modified looped suture